Bridging the Gap: The Relationship between INGO Activism and Human Rights Indicators. Issue 1 (1st January 2019) - Chaudhry, Suparna
Abstract: This article explores the tension between the production of "naming and shaming" reports as tools of activism by international nongovernmental organizations (INGOs) and the usage of these reports as cross-national indicators of human rights violations. Because INGOs are strategic actors, their reports are not a reflection of the "true" levels of abuse. Although existing scholarship has raised this issue in relation to bias in cross-national indicators, it has yet to explain the process by which NGOs produce reports. This article exploits subnational variation across domestic and international NGOs within India, showing how the divergence in their reports can be explained by these groups' organizational structures, probability of success in their chosen issue areas, and target audiences. By explaining how human rights NGOs produce reports, this article concludes with suggestions to ensure that the biases prevalent in a single source of data do not drive the results of future scholarship.